Light and scanning electron microscopy studies of the early infection stages of Hymenoscyphus pseudoalbidus on Fraxinus excelsior. (7th March 2013) - Cleary, M. R.; Daniel, G.; Stenlid, J.
Abstract : The ontogeny and morphology of infection structures associated with the early stages of infection of Hymenoscyphus pseudoalbidus on common ash ( Fraxinus excelsior ) leaves and leaf petioles were investigated using light and scanning electron microscopy. Ascospores were produced in mature ascocarps and infections on ash leaves were first observed 2 weeks later. Ascospores developed germ tubes, followed by appressorium formation and penetration of epidermal cells on ash leaves and petioles. Chalara fraxinea spores, the anamorph of H. pseudoalbidus, appeared and were arranged in chains, surrounded by a membranous sheath, and varied considerably in size and shape. Host invasion and colonization of all cell types of leaves and petioles were observed using light microscopy. The role of leaves and petioles as sites of infection in the life cycle of H. pseudoalbidus and the disease cycle of ash dieback is discussed.